2021
DOI: 10.1177/00469580211067943
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hypothyroidism Patients With Thyroid Hormone Receptor Variants Are Not Rare: A Systematic Review

Abstract: Background Primary congenital hypothyroidism (CH) is a common endocrine and metabolic disease. Various genetic factors, including the thyroid hormone receptor (TSHR), play an important role in CH. Aim To explore the occurrence of pathogenic TSHR variants in CH. Methods We searched published articles in PubMed, Web of Science, and Cochrane Library databases, from the establishment of the database to September 26, 2021. Studies with sequencing partial or full exons of TSHR in CH patients were included. Gene poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
0
1
0
4
Order By: Relevance
“…[9] Previous reports have shown that carriers of homozygous or compound heterozygous mutations are more likely to develop congenital hypothyroidism, while subjects with monoallelic heterozygous mutation in the TSHR gene may present with normal thyroid function or subclinical hypothyroidism. [5,10] According to numerous studies results, 2 modes of inheritance of TSHR inactivation mutations causing diseases are identified including autosomal recessive and autosomal dominant inheritance. [11][12][13] Previous study found that the G132R mutation would reduce cAMP production and binding activity, and the patient had normal thyroid ultrasound and increased TSH level.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Previous reports have shown that carriers of homozygous or compound heterozygous mutations are more likely to develop congenital hypothyroidism, while subjects with monoallelic heterozygous mutation in the TSHR gene may present with normal thyroid function or subclinical hypothyroidism. [5,10] According to numerous studies results, 2 modes of inheritance of TSHR inactivation mutations causing diseases are identified including autosomal recessive and autosomal dominant inheritance. [11][12][13] Previous study found that the G132R mutation would reduce cAMP production and binding activity, and the patient had normal thyroid ultrasound and increased TSH level.…”
Section: Discussionmentioning
confidence: 99%
“…На долю гипоплазии и гемиагенезии приходится 10 и 2% соответственно. Известно, что гипоплазия в ряде случаев обусловлена мутациями в гене TSHR [ 13 ].…”
Section: Discussionunclassified
“…2021 г. [ 13 ], включавшему анализ данных 3975 детей с ВГ из 23 стран (представленных в 44 исследованиях «случай-контроль»), средняя частота патогенных вариантов в гене TSHR составила 7,83%. Частота патогенных вариантов в гене TSHR зависит от популяций и варьирует от 0 (Бразилия) до 29% (Израиль).…”
Section: Discussionunclassified
See 2 more Smart Citations